Pengaruh Subtitusi Agregat Halus dengan Serbuk Cangkang Kerang Dara dan Ampas Kopi Sebagai Subtitusi Parsial Semen terhadap Kuat Tekan Beton Mutu K-175 - Yudha aditya Pamungkas; Rasio Hepiyanto; Yosef Cahyo Setianto (Universitas Batanghari Jambi, 2026)
The rapid growth of the construction industry, particularly the use of concrete, has increased the demand for key raw materials such as cement and sand, which has led to significant environmental issues, including increased CO2 emissions and land degradation due to sand mining. To mitigate these negative impacts, this study focuses on the utilization of waste materials as potential alternative materials, namely oyster shell powder (SKD) as a substitute for fine aggregates and coffee grounds (AK) as a partial substitute for cement. Clam shell powder contains calcium carbonate (CaCO3), which can improve the mechanical quality of concrete, while coffee grounds have pozzolanic properties and silica content. This study used an experimental method conducted in the Civil Engineering Laboratory of UNISLA to determine the compressive strength of concrete after mixing with these two materials and comparing it with normal concrete. Four mixture variations were tested: 0% (normal concrete), 3% SKD + 2% AK, 6% SKD + 4% AK, and 9% SKD + 6% AK. The results of testing the compressive strength of concrete at 28 days showed that the use of these waste substitutes overall reduced the compressive strength of concrete: normal concrete reached 175.01 kg/cm2, followed by the 3% SKD + 2% AK variation at 165.09 kg/cm2, 6% SKD + 4% AK at 157.21 kg/cm2, and the lowest value at 9% SKD + 6% AK at 149.96 kg/cm2. Based on these findings, the higher the percentage of waste mixture, the lower the compressive strength of the concrete produced, and no mixture variation achieved the optimal compressive strength compared to normal concrete.